Carrier Frequency Offset Estimation Techniques in OFDM System: A Survey - Singh, Shampal; Buttar, Avtar Singh (International Journal of Computer Sciences and Engineering, 2014)
Orthogonal Frequency Division Multiplexing (OFDM) has proved it is ability to provide the required services and offer large data rates with sufficient strength to Electromagnetic wave channel destruction The major drawback concern in the OFDM data transmission is loss of orthogonality of signal due to Carrier Frequency Offset (CFO), caused either due to mismatching of frequency of oscillator at transmitter side and receiver side or due to Doppler shift. CFO leads to create problems like Inter carrier interference (ICI) and Signal to Noise plus Interference Ratio decrease (SINR). As a result, the overall capacity of the system is reduced. The estimation of CFO is difficult problem. Researchers have proposed various CFO estimation techniques to compensate the effect of CFO by now. This paper provides major CFO estimation algorithm and techniques in literature briefly along with the analysis of their advantages and disadvantages.